An introduction to medicinal chemistry - Patrick, Graham L. (Oxford University Press, 2001)
For many people, taking some form of medication is part of everyday life, whether for mild or severe illness, acute or chronic disease, to target infection or to relieve pain. However for most it remains a mystery as to what happens once the drug has been taken into the body: how do the drugs actually work? Furthermore, by what processes are new drugs discovered and brought to market?